KARAKTERISTIK PEMBAKARAN SMALL BATCH HUSK GASIFIER DENGAN MENGGUNAKAN VARIABLE SPEED BLOWER - Fernanda, Yolli (Sainstek, 2013)
We made the design for the rice husk gasifier stove with the supply air using a blower. Retrieved reactor diameter is 15 cm and height 70 cm. The maximum operating time obtained is 43 minutes with maximum efficiency approaching 15%. Air supply during the operation of the furnace must be set up to fire over. Comparing with the furnace designed to research conducted by Belonio, 2005, the results was close enough, especially for the operating time and efficiency tools. The problem in this design is fan supplied air supply has current greater than the Belonios design.